2022
DOI: 10.1186/s12888-022-04384-2
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and psychological sub-health among Chinese adolescents: the mediating effect of Internet addiction

Abstract: Background The factors related to psychological sub-health (PSH) have been widely described, but the research on the mechanism behind the complex relationship between childhood trauma and PSH is limited. This study investigated the current situation and risk factors of PSH among Chinese adolescents. And further, explore whether Internet addiction (IA) plays a potential mediating effect in childhood trauma and PSH. Methods The study was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 72 publications
1
8
0
2
Order By: Relevance
“…Childhood trauma(CT) is a global concern; a large number of cross-sectional survey studies found that one-third to one-half of the studied population had experienced CT [ 1 4 ], and the same results were also found in many cohort studies [ 5 10 ]. Studies have found that CT could impact the physical and mental health of people throughout their life [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 79%
“…Childhood trauma(CT) is a global concern; a large number of cross-sectional survey studies found that one-third to one-half of the studied population had experienced CT [ 1 4 ], and the same results were also found in many cohort studies [ 5 10 ]. Studies have found that CT could impact the physical and mental health of people throughout their life [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 79%
“…This may be because adolescents who experience adverse childhood experiences tend to feel less family warmth, have lower self-esteem, have lower self-worth and are more likely to develop addiction problems ( Jhone et al., 2021 ; Hu, 2020 ; Cao et al., 2021 ). Specifically, adverse environments can lead to increased negative emotions, cognitive biases, and reduced social relationships among adolescents, and adolescents are at high risk for emotional regulation disorders ( Yang et al., 2022 ; Xiang et al, 2023 ; Geng et al., 2022 ). Adolescents overuse the internet to satisfy the need to be loved and connected and use the virtual world to cope with isolation and obtain social support, thus self-medicating negative emotions and ultimately leading to the emergence of internet addiction behaviours ( Dong et al., 2021 ; Ma, Huang, & Ma, 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, self-reported psychological symptoms were screened using the multidimensional sub-health questionnaire of adolescents (MSQA), which was developed by Prof. Fangbiao Tao’s team for Chinese adolescents ( Xu et al, 2020 ; Yang et al, 2022 ). This scale has been used in several studies and has good reliability in evaluating Chinese adolescents’ psychological symptoms ( Xu et al, 2019 ; Lu et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%